Seed regulation: challenges and perspectives of Mexican law - Ramírez-Vázquez, Jessica; Rojas-Sandoval, Leticia (Revista Mexicana de Ciencias Agrícolas, 2026)
In Mexico, the Federal Law on Seed Production, Certification and Trade was enacted in 2007; its main objective is to regulate the production, qualification and trade of seeds, seeking to organize and improve the national agricultural sector. This paper analyzes, through a documentary review, the impact of this legislation on the protection and conservation of native seeds in Mexico. Currently, the legal framework, by pointing to a model for the production and certification of ‘improved’ and commercial seeds, systematically marginalizes native varieties and peasant seed systems, which are essential for agricultural resilience and long-term food security. The study concludes that, despite its objectives, the law inadvertently contributes to the loss of agrobiodiversity and genetic erosion in the country. The lack of description guides and the limited inclusion of native varieties in the National Catalog of Plant Varieties leave an invaluable genetic and cultural heritage in a situation of vulnerability.